Hubungan Antara Lingkar Perut dan Volume Ambing dengan Kemampuan Produksi Susu Kambing Peranakan Ettawa - Taofik, Ahmad; Depison, Depison (Fakultas Peternakan Universitas Jambi, 2008)
The Study was conducted to know relationship between stomach circumference and mammary gland volume on milk production ability of crossing Ettawa goat.. The research used descriptif method, the data were taken from 27 of females goat at first lactation. Collected data analyzed using simple regression methode. The Results showed that correlation coefficient of stomach circumference and mammary gland Volume had correlation coefisien 0,660 higher than correlation coefisien of stomach round 0,259. So mammary gland Volume can be used as to predict milk production.